Facilitating Social Presence in the Synchronous and Asynchronous English Language Class in Yogyakarta, Indonesia (Journal of Foreign Language Teaching and Learning, 2023)
Researchers have been interested in the topic of social presence in the areas of communication, online learning, and media. Due to the research's limitations in Indonesia, more research should be done on social presence in online learning in higher education. In contrast to earlier studies, the current study attempted to represent the students’ perspective regarding the occurrence of social presence in the synchronous and asynchronous classroom settings and the strategies used by teachers in synchronous and asynchronous English language instruction at an English Education Department of a private university in Indonesia. The study used a mix-method design using a survey of 89 students concerned with the occurrence of social presence and semi-structured interviews to twelve lecturers related to strategies to create a social presence. The Community of Inquiry Framework developed by Arbaugh et al. (2008) was used. The findings revealed that regarding social presence, most components (seven components) were categorized as high, while the two components were moderate, indicating the occurrence of the social presence elements in the learning process. Lecturers’ strategies to enhance the social presence include affective, cohesive, interactive, informative, imperative, and creative strategies.